ANALISIS SWOT DAN STRATEGI PENGEMBANGAN PADA KEBERHASILAN INDUSTRI KECIL ROTAN KOTA PADANG - Rika Desiyanti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2016)
Rattan commodity in Padang city, including commodity most likely to be developed. With its potential industrial development aimed at strengthening competitiveness through competitive advantages. The strategy used to develop the small industry rattan in Padang city in order to have a competitive edge is SWOT analysis and using the right strategy for businesses rattan industry. The object of research is small rattan Industry, located in Tanah Sirah Kelurahan Pitameh Kecamatan Lubuk Begalung Kota PadangTanah Sirah Kelurahan Pitameh Kecamatan Lubuk Begalung Kota Padang and institutions related. This study uses primary data, field observations, interviews and questionnaires, and secondary data obtained through agencies associated with the research. The analysis was performed by using a SWOT analysis. The result is obtained that rattan industry Padang from the internal side of strength greater than weakness, while on the external side of the existing opportunities greater than the treatness. Rattan industry Padang city were the first quadrant which means that this position indicates that the rattan industry in the city of Padang strong and likely to grow. Keywords: SWOT Analysis, development of the rattan industry